Mahārājā Raṇajīta Siṅgha - Grewal, J. S. (Ammritasara : Niū Eja Buka Saiṇṭara, 1983)
Life and works of Ranjit Singh, 1780-1839, Maharaja of the Punjab.
In Panjabi.
Mode of access: Internet.
Keywords: Ranjit Singh, -- Maharaja of the Punjab, -- 1780-1839.; Sikhs -- Kings and rulers -- Biography; Punjab (India) -- Kings and rulers -- Biography